"The Prophet Muhammad and his Companions" and "Musa va 'UJ": A Comparison of Two Paintings. Issue 1 (2nd January 2020) - Norouzian, Giti
ABSTRACT: This study compares two paintings: one is the third in an undated illustrated manuscript of Kalila va Dimna in the Gulestan Palace Library in Tehran, and the other, often called " Musa va 'Uj", is in the Khalili Collection in London. These two paintings share so many similarities that they have long been thought to be the work of the same hand, painted at about the same time. The aim of this article is to examine the proposition by considering some relevant historical and aesthetic aspects. The study of the differences and similarities between the two paintings should be helpful in suggesting a resolution to this interesting problem.